Study of working conditions in aluminum casting shops worksites - A. M. Lazarenkov; I. A. Ivanov (Литьë и металлургия)
The results of the study of working conditions in aluminum casting shops worksites are presented. The results of these studies showed that in worksites there are exceedance of the permissible limits for noise, vibration, the content of harmful substances in the working environment, intensity of infrared (thermal) radiation and air temperature. There is effect of electromagnetic radiation on the workers during the service of induction furnaces. In addition, the main harmful production factors include the severity of work and the intensity of the labor process. The efficiency of the protective screens of the IAT-6 induction crucible furnace was evaluated.